From millennium development goals to sustainable development goals through informal cross-border trading: an escape for the poor in a suffocating national economy in Gweru, Zimbabwe - Dzawanda, Beauty; Matsa, Mark (Springer Cham, 2022)
Informal cross-border trading can help to achieve the sustainable development goals through positive macroeconomic and social ramifications, such as income creation and food security, especially for poor households. This research examines how the informal cross-border trading is achieving sustainable development goals in a challenging economic situation in Zimbabwe. Qualitative design was used as a method, as it allowed the collection of detailed information from the participants through semi-structured interviews, which was the major data collection tool. Twenty-five informal cross-border traders were selected through snowball sampling. Secondary data was used for comparative analysis in order to reveal the achievements of the millennium development goals and the sustainable development goals by the informal cross-border trading before and during the cash crisis, since this research was undertaken during Zimbabwe’s cash crisis economy period. Data analysis was done from an interpretive approach using thematic analysis. The results revealed that the informal cross-border trade plays a vital role in achieving, particularly the millennium development goals 1, 2 and 3 and the sustainable development goals 1, 2, 4 and 5. The informal cross-border trading improves the lives of those who are engaged in it through poverty alleviation, income creation, employment creation and by improving food security. The income created from the informal cross-border trade assists traders in accessing different goods and services needed for survival. The research recommends a strong support from the Zimbabwean government to this sector as it is a potential medium for achieving the sustainable development goals.